Ambient temperature and preterm birth: A retrospective study of 32 million US singleton births - Shengzhi Sun; Kate R. Weinberger; Keith R. Spangler; Melissa N. Eliot; Joseph M. Braun; Gregory A. Wellenius (Environment International, 2019)
Background: Days of extreme temperature may be associated with transiently higher risk of preterm birth, but prior studies have been limited and results have been heterogeneous. Objectives: To evaluate the association between days of extreme heat and cold and risk of preterm birth among ~32 million live singleton births between 1989 and 2002 across 403 counties in the contiguous United States (US). Methods: We used a distributed lag nonlinear model to estimate the association between population-weighted daily mean temperature and risk of preterm birth in each county and then pooled results across geographic regions and climate zones. We defined extreme heat and cold as the 95th and 5th percentile of the county-specific temperatures, respectively. Results: Preterm birth accounted for 9.3% of deliveries. There was a monotonic association between ambient temperature and risk of preterm birth. Days of extreme heat and cold were associated with a relative risk of preterm birth of 1.025 (95% CI: 1.015, 1.036) and 0.985 (95% CI: 0.976, 0.993) over the subsequent four days, respectively, relative to the county-specific median temperature. If causal, the fraction of preterm births attributable to extreme heat was 0.17% (empirical 95% CI: 0.14%, 0.19%), corresponding to 154 (empirical 95% CI: 127, 173) preterm births per million births. Extreme heat was more strongly associated with preterm birth in regions with colder and drier climates, and among younger women. Days of extreme cold temperature were associated with lower rather than higher risk of preterm birth. Conclusions: Days of extreme heat, but not extreme cold, are associated with higher risk of preterm birth in the contiguous US. If causal, these results may have important implications for the management of pregnant women during forecasted periods of extreme heat. Keywords: Heat, Cold, Preterm birth, Birth cohort, United States